Sequential injection differential pulse voltammetric method based on screen printed carbon electrode modified with carbon nanotube/Nafion for sensitive determination of paraquat - Prakit Chuntib (2018)
© 2017 Elsevier B.V. The screen-printed carbon electrode (SPCE) modified with various nanoparticles has been studied for using as a working electrode in voltammetric technique. The electrochemical behavior of paraquat on different electrodes was studied by cyclic voltammetry (CV), and then differential pulse voltammetry (DPV) has been employed for trace analysis of paraquat based on redox reaction which the peak current was directly proportional to the concentration of paraquat in the solution. The SPCE modified with carbon nanotube dispersed in Nafion and ethanol (SPCE-CNT/Nafion) gave the best result. Sequential injection-differential pulse voltammetric (SI-DPV) method has been developed for more automated analysis and to reduce chemical consumption. The parameters affecting the SI-DPV system such as step potential, modulation amplitude, flow rate, and concentration of sodium chloride as an electrolyte were studied to improve the sensitivity. Under the optimum condition of the system, i.e., Nafion concentration of 1% (w/v), volume of CNT suspension of 2 µL, flow rate of 100 µL s−1, step potential of 5 mV, modulation amplitude of 100 mV and concentration of sodium chloride of 1 M, a linear calibration graph in the range of 0.54–4.30 µM with a good R2of 0.9955 and a limit of detection of 0.17 µM (0.03 mg L−1) were achieved. The proposed system shows high tolerance to some possible interfering ions in natural water, surfactant, and other pesticides. The relative standard deviation (RSD) was 4.2% for 11 replicate measurements with the same electrode. The reproducibility for the preparation of 7 modified electrodes was 2.3% RSD. Recoveries of the analysis were obtained in the range of 82–106%. The developed system can be conveniently applied for analysis without pretreatment of the samples.